Development of Tourism Villages Based on Promotion Integration Through Websites - Sayekti Suindyah Dwiningwarni; Mei Indrawati; Machrus Ali; Syamsiyah Yuli Dwi Andari (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
Galengdowo Village has both natural and artificial tourism potential. The problem is that the promotion has not been carried out optimally and has not been integrated into one website and the lack of tourist information for prospective tourists. The goal of this action is to progress tourist villages through digitization and web sites. The methods used are training, mentoring, supervising, and asessment. The findings indicate this the tutoring and assistance in operating the web and the design of the promotion greatly impact the participants, it can regarded the finding of monitoring through the galengdowo. id web. he tourist information center is very much needed by the manager because it can provide information about tourist attractions to tourists. The results of the organizational management training, namely increasing the quality of Pokdarwis managers, which initially did not have a job description and after the training, there was a job description for each administrator